An Online Neonatal Intensive-Care Unit Monitoring System for Hospitals in Nigeria - Idowu, Peter Adebayo; Asahiah, Franklin Oladiipo; Balogun, Jeremiah Ademola; Olusanya, Olayinka Olufunmilayo (International Journal of Biomedical and Clinical Engineering, 2020)
International Journal of Biomedical and Clinical Engineering, volume 6 No,1,p.1-2.